We came to you with flowers blooming walls. In memory of Kost Prysiazhnyi - Kazantseva, Tetiana; Bilinska, Oksana (Видавництво Львівської політехніки, 2016)
The article is devoted to historical aspects of the greening of buildings at the example of Lviv city. Based on iconographic and field research, jardinieres (stands for placing pots of flowers), fences and trellis for climbing plants have been investigated. Directions for the usage of greening to humanize the appearance of buildings and to increase the attractiveness of the historical city have been provided. Стаття присвячена аспектам історичного озеленення будівель на прикладі Львова. На основі іконографічних та натурних досліджень виділено особливості застосування жардиньєрок (для розміщення вазонів з квітами), трельяжів та огорож для витких рослин. Розкрито напрямки використання озеленення будівель для гуманізації та підвищення атрактивності історичного міста.
До вас із квітами. квітнучі стіни. Пам’яті Костя Присяжного
Keywords: historic buildings greening; Lviv; jardinieres and trellis for climbing plants; gardening to humanize and increase attractiveness of the historical city; історичне озеленення будівель; Львів; жардиньєрки та трельяжі для витких рослин; озеленення для гуманізації та підвищення атрактивності історичного міста